Relação entre as opções estratégicas e os elementos de gestão estratégica de custos: um estudo em companhias listadas na BM&FBOVESPA - Santana, Tatiainy Afonso das Mercês (Universidade do Vale do Rio dos Sinos, 2017)
This study aimed to analyze relationship between strategic options and elements of strategic cost management in companies listed on the Stock Exchange, Commodities and Futures (BM & FBOVESPA). A survey in the financial year 2015 Management Reports was conducted (n=40); for data classification, a predefined categories and subcategories checklist based on Strategic Cost Management and Multiple Linear Regression Analysis - Stepwise Method. Results supported eight hypotheses, which deducing that the three strategic approaches (strategic typology, competitive and strategic mission) are related to certain strategic cost management elements use. It was observed a greater element citation related to costs and structural determinants analysis by prospective and differentiation advantage companies. As regards the mission, the “in hold” companies make greater strategic cost management element citation related to customer actions, suppliers and strategic pricing of products. No relationship was found between the strategic options and the activity-based costing / activity-based management, total cost ownership, quality cost management and production capacity use. The significant relationship found between the analytical typology and certain elements of strategic cost management, not only confirms the initial hypothesis, but also show a novelty, since such a relationship was not evidenced in previous studies.
Keywords: Relação; Opções estratégicas; Elementos de gestão estratégica de custos; Relationship; Strategic options; Strategic cost management elements; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis